DAMPAK APLIKASI PAJAK KENDARAAN DIGITAL NASIONAL SIGNAL DALAM MENINGKATKAN KEPATUHAN WP - Kadek Wulandari Laksmi; Rommy Patrik Liyanto (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2024)
Motor Vehicle Tax (PKB) represents a form of local taxation. Since 2021, the government has introduced the Samsat Digital (SIGNAL) application, streamlining the fulfillment of tax obligations for taxpayers. The objective of this research is to assess the acceptability of this application among taxpayers in accordance with TAM (Technology Acceptance Model) theory, with the aim of enhancing taxpayer compliance. The methodology employed involves a descriptive statistical approach, focusing on the population of taxpayers in the city of Denpasar utilizing the SIGNAL application. The analysis utilizes multiple linear regression to evaluate the impact of variables such as convenience, benefit, and security on taxpayer compliance. The findings indicate that these variables have a statistically significant positive influence on taxpayer compliance. The implications of this research provide further understanding of the demographic characteristics of SIGNAL app users, which can form the basis of further marketing or development strategies in increasing technology acceptance among age groups.